Do It, Don’t Feel It, and Be Invincible: A Prolog of Exercise Addiction in Endurance Sports - Nogueira, Abel; Tovar-Gálvez, Maribel; González-Hernández, Juan (Frontiers in Psychology, 2019)
The social relevance of endurance sports has increased people’s motivation to engage in these particular physical activities, associating their practice with a particular lifestyle (e.g., feeling victorious and a feeling of self-improvement). Therefore, the dark personality traits (not because they are negative but because they are more hidden), understood as a personal and adaptive response to the psychosocial relationships that athletes establish while practicing these sports. Following these arguments, Grit has been used to trace the response of athletes in their quest to improve performance and endurance in the face of common setbacks suffered as a result of long hours of training. Empirical studies should help to discover how these personality traits can pose real challenges to their adaptation, and what the impact of their psychological response may be in a functional or dysfunctional way [e.g., exercise addiction (EA)], in order to classify them as risk or protective factors. Through transversal design, the present study sought to explore the relationship between Grit and Dark Traits of Personality regarding the appearance of EA in a sample (N = 241) of amateur endurance sport athletes (Mage = 31.80; SD = 9.87). The results show that men not only score higher for addiction levels but also for narcissism (grandiosity feelings) and psychopathy (coldness) factors. If signs of narcissism and Machiavellianism increase, perseverance efforts grow too, and the likelihood of EA increases considerably. The conclusions drawn on the basis of the results allow us to place consistency of interest as a protective factor for the EA, whereas Dark Traits of personality – especially Machiavellianism – constitute a risk factor.